Endoscopic diagnosis and treatment of biliary obstruction due to acute cholangitis and acute pancreatitis secondary to Fasciola hepatica infection. - DOLAY, KEMAL; DOLAY, KEMAL; MALYA, FATMA ÜMİT; HASBAHCECI, MUSTAFA; AKÇAKAYA, ADEM; HATIPOĞLU, ENGİN; Ümit, Malya; Akçakaya, ADEM (My University, 2018)
In the differential diagnosis of biliary obstruction with unknown etiology, biliary fascioliasis should be considered in endemic and nonendemic regions. After diagnostic evaluation, endoscopic retrograde cholangiopancreatography (ERCP) was performed for etiological evaluation and/or treatment of biliary obstruction in five patients with a mean age of 55.8 years. Endoscopic sphincterotomy and cholangiogram revealed linear filling defects in the biliary system. Fasciola hepatica parasites were extracted using balloon and basket catheters in two and three patients, respectively. No morbidity or mortality was observed. F. hepatica infection should be considered as a differential diagnosis of biliary obstruction with unknown etiology in endemic and non-endemic regions. ERCP can be the standard diagnostic and/or therapeutic procedure in cases of biliary obstruction due to fascioliasis. Due to slippery and gel-like characteristics of the parasite, use of a basket catheter in semi-opened position may be required in case of unsuccessful extraction using a balloon catheter.